Production of Ceramic Brick Based on Aluminum-Silicate Wastes; Key Engineering Materials; Vol. 683 : Multifunctional Materials: Development and Application - Vlasov V. A. Viktor Alekseevich; Skripnikova N. K.; Yuriev I. Y.; Kosmachev P. V.; Litvinova V. A.; Nikonenko E. L. Elena Leonidovna (Physicochemical Properties of Materials and Current Processing Technologies, 2016)
Title screen